Anatomické poznámky k miniinvazivní dlahové osteosyntéze proximálního humeru - kadaverózní studie - Křivohlávek, M; Taller, S; Lukáš, R; Dráč, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2014)
PURPOSE OF THE STUDY: The aim of the study was to assess the average length of a proximal and a distal incision, to verify the location of the axillary nerve and to identify risk factors for nerve injury during minimally invasive plate osteosynthesis. MATERIAL AND METHODS: During cadaver study a total of 24 implantations using the Philos angular stable plate were performed from the minimally invasive anterolateral approach. A five-hole plate inserted with the aid of new Philos aiming device was used in all cases. The plate was fixed with four screws proximally and with three screws to the diaphysis. After implantation either of the incisions were joined and the axillary nerve was exposed on the lateral side of the arm. RESULTS: The nerve was not found to be injured during plate implantation in any of the cases. The average length of the proximal incision was 56 ± 2.8 mm (52-64 mm) and that of the distal incision was 32 ± 2.5 mm (28-35 mm). The middle free part covering the axillary nerve was on average 45 ± 4.3 mm (38-54) long. The average width of the nerve was 1.9 ± 0.35 mm (1.4-2.8 mm). The average distance of the axillary nerve was 39 ± 2.9 mm (37-44 mm) from the superior facet of the greater tubercle and 53 ± 3.9 mm (48-60) from the lower edge of the acromial process. In 80% of the cases the nerve was located in the area determined for the screws going to the medial calcar region; in 20% it was over a hole for the screw directed towards the centre of humeral head. Nerve location above the first six most proximally placed screws was not recorded in any of the cases. DISCUSSION: The minimally invasive anterolateral approach is an alternative technique for osteosynthesis of proximal humerus fractures using angular stable plates. Advantages reported by a number of authors include lower incidence of avascular necrosis of the humeral head, an easier way of reduction and a better view of the rotator cuff. On the other hand, this approach is associated with a higher risk of damage to the axillary nerve. Distance of axillary nerve from acromion is very variable. It may be located in the range of 30 to 85 mm from the acromial edge. CONCLUSION: The anterolateral approach is, when respecting the anatomical position of the axillary nerve, a safe alternative to the conventional deltoideopectoral approach.
Keywords: Minimally Invasive Surgical Procedures; humerus; Axilla; Fracture Fixation, Internal; Bone Plates; vnitřní fixace fraktury; Peripheral Nerve Injuries; Intraoperative Complications; peroperační komplikace; fraktury humeru; Humerus; hodnocení výsledků zdravotní péče; lidé; Humeral Fractures; kostní destičky; Humans; poranění periferního nervu; axila; miniinvazivní chirurgické výkony; Outcome Assessment, Health Care